2014
DOI: 10.1590/s0100-69912014000100003
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous core biopsy of palpable breast lesions: accuracy of frozen section histopathological exam in the diagnosis of breast cancer

Abstract: frozen section histopathological findings showed excellent correlation with the findings by the technique in paraffin in the fragments of palpable breast tumors obtained by thick needle percutaneous core biopsy (98.2% accuracy). Therefore, in these patients, it was possible to anticipate the diagnosis, staging and the breast cancer treatment planning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 22 publications
1
5
0
1
Order By: Relevance
“…Specificity and PPV was 100% while NPV was 95.45% which was equaled to the findings reported by Tarek et al [20] and Kumar et al [25]. The diagnostic accuracy of frozen section was 98%, similar to that of Dos Santos et al [26]. When FNAC and frozen section were compared, it found that the accuracy of frozen section was more than FNAC which is same as in previous studies [20,25].…”
Section: Discussionsupporting
confidence: 86%
“…Specificity and PPV was 100% while NPV was 95.45% which was equaled to the findings reported by Tarek et al [20] and Kumar et al [25]. The diagnostic accuracy of frozen section was 98%, similar to that of Dos Santos et al [26]. When FNAC and frozen section were compared, it found that the accuracy of frozen section was more than FNAC which is same as in previous studies [20,25].…”
Section: Discussionsupporting
confidence: 86%
“…Percutaneous image‐guided biopsy is a minimally invasive and targeted approach to tissue sampling with an overall high diagnostic yield. When compared to open surgical biopsy, image‐guided percutaneous biopsy offers similar diagnostic rates 2–32,49 with overall lower morbidity 3,24,25 . However, up to 15% of these procedures are associated with yielding nondiagnostic tissue.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, percutaneous, image‐guided biopsies have increasingly gained popularity in the diagnostic work‐up of musculoskeletal neoplasms. This technique offers a minimally invasive and targeted approach to tissue sampling, with similar rates of the successful yield of diagnostic tissue, ranging anywhere from 68% to 96% 2–32 . The complications associated with image‐guided biopsies are generally rare and typically self‐limiting 5,6,18,22,33 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations